Analysis of the Use of Activity Based Management (ABM) as an Instrument to Increase Cost Efficiency: Analisis Penggunaan Activity Based Manajement (ABM) sebagai Instrumen untuk Meningkatkan Efisiensi Biaya - Hendika, Putri; Pitri Musliati; Selly Nadia (Jurnal Perilaku Bisnis Kontemporer, 2024)
The Putri Tunggal tofu factory is a business that processes soybeans into raw tofu. Management can use Activity Based Management (ABM) as the main tool to streamline costs related to business activities to maximize profits. The research method used is qualitative descriptive analysis. The results of the research on the Putri Tunggal Tofu Factory business are that non-value added activities that can be eliminated are the transfer of soybean starch to cement tubs and the cutting of tofu that has been molded. Meanwhile, non-value added activities that cannot be eliminated are soaking soybeans for 4 hours, packaging, and checking the quality of finished goods.